Four weeks of augmented eccentric loading using a novel leg press device improved leg strength in well-trained athletes and professional sprint track cyclists - Harden, M.; Wolf, A.; Evans, M.; Hicks, K. M.; Thomas, K.; Howatson, G. (PLOS ONE, 2020)
This study assessed the efficacy of strength training using augmented eccentric loading to provoke increases in leg strength in well-trained athletes, and sprint track cyclists, using a novel leg press device. Twelve well-trained athletes were randomly allocated traditional resistance training (TRAD, n = 6), or resistance training using augmented eccentric loading (AEL, n = 6). A further 5 full-time, professional sprint track cyclists from a senior national squad programme also trained with augmented eccentric loading (AEL-ATH) alongside their usual sport-specific training. Participants completed four weeks of twice-weekly resistance training using the leg press exercise. In TRAD the lowering phase of the lift was set relative to concentric strength. In AEL and AEL-ATH the lowering phase was individualised to eccentric strength. Concentric, eccentric, isometric and coupled eccentric-concentric leg press strength, and back squat 1 repetition maximum (1RM), were assessed pre- and post-training. The AEL and AEL-ATH groups performed the eccentric phase with an average 26 ± 4% greater load across the programme. All groups experienced increases in concentric (5%, 7% and 3% for TRAD, AEL & AEL-ATH respectively), eccentric (7%, 11% and 6% for TRAD, AEL & AEL-ATH respectively), and squat 1RM (all p < 0.05), where the AEL-ATH group experienced relatively greater increases (13% vs. 5% in TRAD and AEL, p < 0.01). The TRAD and AEL groups also increased isometric strength (p < 0.05). A four-week period of augmented eccentric loading increased leg strength in well-trained athletes and track cyclists. The eccentric leg press stimulus was well-tolerated, supporting the inclusion of such training in the preparation programmes of athletes.